2012
DOI: 10.1089/ten.tea.2011.0157
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Chondrogenic Differentiation Potential of Human Gingival Fibroblasts by Spheroid Formation on Chitosan Membranes

Abstract: Human gingival fibroblasts (HGF) were recently found to be a source of mesenchymal stem cells. Their behavior on a biomaterial has not been reported so far. The effect of culturing HGF on chitosan membranes on their chondrogenic differentiation was investigated in this study. HGF were first cultured on chitosan membranes and spheroid formation of HGF was observed. Next, HGF on chitosan were induced with chondrogenesis induction medium and their chondrogenic differentiation potential was expressed by assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…35 In the field of cartilage tissue engineering, spheroid formation provides a 3D architecture that enhances chondrogenic differentiation capacity. 36,37 Previous studies have demonstrated that HA and 3D spheroid culture systems using photolithography techniques can promote MSCs to form spheroids. 23,38 Motivated by the urgent need for more efficient cartilage tissue engineering platforms and by the potential of stem cell-based therapies, we sought to assess the combined effects of matrix nanotopography and HAmediated signaling on the chondrogenic differentiation of DPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…35 In the field of cartilage tissue engineering, spheroid formation provides a 3D architecture that enhances chondrogenic differentiation capacity. 36,37 Previous studies have demonstrated that HA and 3D spheroid culture systems using photolithography techniques can promote MSCs to form spheroids. 23,38 Motivated by the urgent need for more efficient cartilage tissue engineering platforms and by the potential of stem cell-based therapies, we sought to assess the combined effects of matrix nanotopography and HAmediated signaling on the chondrogenic differentiation of DPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Meretoja [6] reported that the chondrogenesis was enhanced in co-cultures with articular chondrocytes and MSCs (mesenchymal stem cells). The gingival fibroblast was recently found to be a source of mesenchymal stem cells [7]. Recent study reported the condrogenic differentiation potential of human gingival fibroblasts can be enhanced by spheroid formation on chitosan membranes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro work has suggested that 3D spheroids of MSCs may possess better differentiation capacity than single cells (Huang et al, 2011;Hsu et al, 2012a). MSC spheroids thus have the potential to replace MSC single-cell suspension for use in tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs grown on these substrates were self-assembled into 3D cellular spheroids that kept migrating on the substrates. The self-renewal property and chondrogenic differentiation potential were significantly enhanced in these substrate-derived MSC spheroids (Huang et al, 2011;Hsu et al, 2012a). Although MSC spheroids are considered superior to single suspended cells in general, the delivery of relatively bulky spheroids without losing their 3D structure is a challenging task.…”
Section: Introductionmentioning
confidence: 99%